THE EFFECT OF RUNNING DICTATION TECHNIQUE TOWARDS STUDENTS’ READING COMPREHENSION AT THE SECONDGRADE STUDENTS OF SMPN 4 BATUKLIANG UTARAIN ACADEMIC YEAR 2017/2018 - Ni Made Pegy Natasia Putri; Muhammad Muhlisin (JUPE : Jurnal Pendidikan Mandala, 2020)
This research is aimed at finding out whether or not Running Dictation technique effective towards students’ reading comprehension at the second grade students of SMPN 4 Batukliang Utara in academic year 2018/2019. The research was quasi experimental design with non-equivalent control group design. The instrument used was multiple choice test (narrative text) which consisted of 25 questions and to collect the data used for pre-test and post-test. The population of the study was the second grade students of SMP Negeri 4 Batukliang Utara, which consisted of two classes with the total number of the students were 40 students. The researcher taken the sample by using total population sampling technique.The data was analysis using statistical formula of t-test. The statistical of the data gathered has been already counted. In this term, the result of the value, it is needed consult t-table by using N-1 as the degree freedom (df). The df is N-1 = 20-1= 19, having known the value of df, the researcher needed to cheeked up the t-table of df19. Theresearcher found that the value t-table was 2.093 for confidence level of 0.05 (95%) and the value t-test was 2.168. t-test was higher than t-table (2.168 > 2.093). In which t-test value was significant. Therefore, it can be concluded that Running Dictation technique is effective towards students’ reading comprehension at the second grade students of SMPN 4 Batukliang Utara in academic year 2018/2019.